2002
DOI: 10.1046/j.1365-2648.2002.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing adverse drug reactions: an orphan task

Abstract: The identification of previously unattended problems, together with the views of service users, suggests that empowering nurses to address the 'care gaps' in medication management may benefit service users. The 'checklist evaluation' approach warrants further investigation, ideally in conjunction with nurse prescribing initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 73 publications
2
52
0
Order By: Relevance
“…When responsibilities are not clearly designated or seen as central to one's role and professional identity [44], they may be missed as each professional assumes the other is taking responsibility. This idea is supported by Dean [45] who in a prospective study of prescribing found that ''many doctors did not consider the task of prescribing important'' beyond putting the patient on a named medicine.…”
Section: Data Flowmentioning
confidence: 99%
“…When responsibilities are not clearly designated or seen as central to one's role and professional identity [44], they may be missed as each professional assumes the other is taking responsibility. This idea is supported by Dean [45] who in a prospective study of prescribing found that ''many doctors did not consider the task of prescribing important'' beyond putting the patient on a named medicine.…”
Section: Data Flowmentioning
confidence: 99%
“…This is when the issue does not clearly fall within the realms of any one health professionals' defined tasks or responsibilities, so each group of health professionals assume or expect that another health professional involved in the patient's care will take responsibility and ask about swallowing problems. 19,27 These findings warrant further investigations before any conclusions may be drawn as there is currently no data to suggest one interpretation is more correct than the other.…”
Section: Discussionmentioning
confidence: 94%
“…The results reported in this article suggest that to engage the students in theoretical sessions, they need to be as clinically applied as possible. Previous criticisms of pre-registration delivery failing to link the theory of pharmacology to practice are reiterated in these findings (Jordan, 2002;Banning, 2004;Turner et al, 2007Turner et al, , 2008. The challenge is for the planning and delivery of course content to engage students and deliver clinically-relevant medicines management training.…”
Section: Key Pointsmentioning
confidence: 99%
“…Criticisms of educational provision include the use of traditional teaching methods to teach pharmacology as a science subject, which fails to relate biological and pharmacological theory to clinical settings (Jordan, 2002;Morrison-Griffiths et al, 2002;Banning, 2004;Turner et al, 2007Turner et al, , 2008, and an over-reliance on the continuous assessment of medicine management competencies by busy, possibly over-stretched, clinical mentors. There has also been a lack of agreement with regard to the emphasis that pharmacology should receive in the curriculum, and/ or whether it should have a discrete identity (e.g.…”
mentioning
confidence: 99%